Between-day reliability and usefulness of a fitness testing battery in youth sport athletes: Reference data for practitioners - Sawczuk, B. J.; Sean S.; Jonathan W.; Read, D.; Costello, N.; Darrall-Jones, J. D.; Stokes, K.; Till, K. (Measurement in Physical Education and Exercise Science, 2018)
This study aimed to evaluate the between-day reliability and usefulness of a fitness testing battery in a group of youth sport athletes. Fifty-nine youth sport athletes (age = 17.3 ± 0.7 years) undertook a fitness testing battery including the isometric mid-thigh pull, counter-movement jump, 5-40 m sprint splits, and the 5-0-5 change of direction test on two occasions separated by 7 days. Usefulness was assessed by comparing the reliability (typical error) to the smallest worthwhile change. The typical error was 5.5% for isometric mid-thigh pull and 3.8% for counter-movement jump. The typical error values were 2.7, 2.5, 2.2, 2.2, and 1.8% for the 5, 10, 20, 30, and 40 m sprint splits, and 4.1% (left) and 5.4% (right) for the 5-0-5 tests. The smallest worthwhile change ranged from 1.1 to 6.1%. All tests were identified as having "good" or "acceptable" reliability. The isometric mid-thigh pull and counter-movement jump had "good" usefulness, all other tests had "marginal" usefulness. ABSTRACT FROM AUTHOR